Debiasing the Mind Through Meditation - Hafenbrack, Andrew C.; Kinias, Zoe; Barsade, Sigal G. (Psychological Science, 2014)
In the research reported here, we investigated the debiasing effect of mindfulness meditation on the sunk-cost bias. We conducted four studies (one correlational and three experimental); the results suggest that increased mindfulness reduces the tendency to allow unrecoverable prior costs to influence current decisions. Study 1 served as an initial correlational demonstration of the positive relationship between trait mindfulness and resistance to the sunk-cost bias. Studies 2a and 2b were laboratory experiments examining the effect of a mindfulness-meditation induction on increased resistance to the sunk-cost bias. In Study 3, we examined the mediating mechanisms of temporal focus and negative affect, and we found that the sunk-cost bias was attenuated by drawing one’s temporal focus away from the future and past and by reducing state negative affect, both of which were accomplished through mindfulness meditation.